2017
DOI: 10.1242/dmm.029108
|View full text |Cite|
|
Sign up to set email alerts
|

An alternative surgical approach reduces variability following filament induction of experimental stroke in mice

Abstract: Animal models are essential for understanding the pathology of stroke and investigating potential treatments. However, in vivo stroke models are associated, particularly in mice, with high variability in lesion volume. We investigated whether a surgical refinement where reperfusion is not reliant on the Circle of Willis reduced outcome variability. Mice underwent 60 min of transient middle cerebral artery occlusion avoiding ligation of the external carotid artery. During reperfusion, the common carotid artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Here, the degree of weight loss over 49 days did not directly correlate with initial damage at 48 h, suggesting that post-stroke weight loss may be caused by factors secondary to the initial injury, and develop during recovery. Experimental models of stroke involving permanent external carotid ligation have been proposed to cause feeding difficulties that result in weight loss [59,60]. Although food intake is likely to be reduced in the initial few days after stroke, we observed that when weight loss was maximal (day 14), food intake was not different (in obese) or increased (in controls) compared to pre-surgery, which is in agreement with others showing no reduction in food intake 7 days after stroke in mice [54].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the degree of weight loss over 49 days did not directly correlate with initial damage at 48 h, suggesting that post-stroke weight loss may be caused by factors secondary to the initial injury, and develop during recovery. Experimental models of stroke involving permanent external carotid ligation have been proposed to cause feeding difficulties that result in weight loss [59,60]. Although food intake is likely to be reduced in the initial few days after stroke, we observed that when weight loss was maximal (day 14), food intake was not different (in obese) or increased (in controls) compared to pre-surgery, which is in agreement with others showing no reduction in food intake 7 days after stroke in mice [54].…”
Section: Discussionmentioning
confidence: 99%
“…In order to allow animals to progress through the functional tests we used non-invasive MRI scanning for quantification of lesion volume. MRI has been shown, in animal stroke models, to detect the evolving ischemic damage and allows a multi-parametric analysis of tissue status [13, 32]. T2 weighted images allow tissue damage to be characterized which reflects final infarct volume, correlates with clinical deficit and identifies tissue damage early following stroke.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously in detail [13] MRI scanning was performed on a 9.4T Agilent scanner (Agilent Technologies, Santa Clare, CA, USA) with a 310 mm bore diameter and 12 cm inner-diameter gradient (600 mT/m maximum gradient strength), interfaced with a DirectDrive Console. Diffusion tensor imaging (DTI) and T2-weighted (T2w) images were acquired at 48h post-MCAO.…”
Section: Methodsmentioning
confidence: 99%
“…109 The group utilised Longa's 42 transient iMCAO method in rats, with both filament insertion and MSC injection via a transected ECA, with the CCA temporarily tied for the duration of iMCAO. 109 CCA repair, reported previously to be successful in rats, 110,111 alongside our recent method development in mice, 101,105 would negate the requirement to transect the ECA, therefore, removing the negative welfare outcomes reported following ECA transection. 102,103,110 Although many IA stem cell delivery experimental models utilise rats, there are examples of these studies conducted in mice.…”
Section: Scientific Applications Of Refinementsmentioning
confidence: 91%